Analysis of Physical and Psychological Consequences of Cancer with an Emphasis on Spirituality-Based Palliative Care Training Program - Sabetsarvestani, Parisa; Karimi, Shahnaz; Dehghan, Azizallah (International Journal of Psychosocial Rehabilitation, 2020)
The prevalence of cancer and its significant effects on all aspects of patients’ lives increase; the concept of life quality and its related factors are overlooked in patients with cancer in Iran, and no studies have examined the effect of spirituality-based palliative care on these patients. Considering all these, the researcher intended to analyze the effect of the spirituality-based palliative care training program on pain, life quality, and nausea and vomiting in cancer patients so that an effective step can be taken in the care process of these patients using the results of the study. The study method was theoretical using a library approach. Books and papers related to the study topic were used for data collection. Multidimensional Model for Understanding Cancer Pain, pain treatment interventions, nursing measures to reduce nausea and vomiting, life-quality measurement methods, characteristics of palliative care, palliative care outcomes, and palliative care role in cancer treatment were examined. According to the results, religious beliefs could have a significant role in life quality enhancement of these patients. Therefore, more effective steps can be taken in improving the quality of life and even using religious beliefs as a kind of therapeutic strategy by strengthening these beliefs through religious programs and meetings for cancer patients and knowing their morale and religious views.